La inteligencia emocional como herramienta pedagógica para un mejor rendimiento escolar en niños y niñas de 5 años de edad del subnivel de preparatoria en la Unidad Educativa Ángel Polibio Cháves del cantón Guaranda, provincia Bolívar, periodo 2021-2022. - Guerrero Meza, Karen Jazmín (2022)
The present investigation refers to the correct management of emotions since currently education not only focuses on learning content mechanically but also on meaningful learning achieved through self-control, empathy, teamwork, coexistence. and social relationships. This research is carried out under the search for credible authors on the subject of emotional intelligence in children where they show us that education in emotions is essential for academic performance, in addition, to contribute in situations of daily life of the infant, by effect collaborating in the labor work of the teacher and the parents. Everything mentioned above was carried out through a guide of playful activities aimed at recognizing and strengthening emotional intelligence. The investigation was carried out in the ¨Unidad Angel Polibio Chaves¨, located in the city of Guaranda, Bolívar province with a number of 33 boys and girls from the high school sublevel